COMPARISON STUDY OF ENERGY EXPENDITURE CALCULATION BETWEEN CONVENTIONAL METHOD AND IRETON-JONES METHOD FOR CRITICALLY ILL PATIENT - Suhartini Ismail; Rizqi Nursasmita (Belitung Raya Foundation, Indonesia, 2017)
Background: The critically ill patients are having nutrition problems in dealing with the critical condition. The problem of nutrition is demanding on the severity of illness. Therefore, the ICU nurses should understand how nutrition can support the patients’ recovery. Objective: This study’s aim was to compare the result of energy expenditure calculation of conventional method with Ireton-Jones method for critically ill patients in the intensive care unit. Methods: This was a comparative and cross-sectional study which recruited 40 samples. The samples were divided into two groups, conventional group method and Ireton-Jones group method, and they met the inclusion criteria. The sample of this study was determined by convenience sampling. To answer the hypothesis, the hypothesis test used Independent sample t-test. Results: The results revealed that there is no significance difference between energy expenditure calculation conventional method and Ireton-Jones method statically. In the other word, either used the conventional method or the Ireton Jones method, the result of energy expenditure calculation has statically significant difference. Conclusion: It can be concluded that the nurse can use both methods to calculate the energy expenditure for critically ill patients to meet their nutrition need. We suggest that for further investigation will recruit many samples and do control of other factors that might be influenced in the study.